If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3 + -4x + -10 = 27 Reorder the terms: -3 + -10 + 5x + -4x = 27 Combine like terms: -3 + -10 = -13 -13 + 5x + -4x = 27 Combine like terms: 5x + -4x = 1x -13 + 1x = 27 Solving -13 + 1x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 1x = 27 + 13 Combine like terms: -13 + 13 = 0 0 + 1x = 27 + 13 1x = 27 + 13 Combine like terms: 27 + 13 = 40 1x = 40 Divide each side by '1'. x = 40 Simplifying x = 40
| 2+2x/7+5-x/5+48/35 | | 3x^9-15x^8=9x^7 | | X^2-12X-676=0 | | 5(5x-3)+11=3 | | -2[5(x-2)-10]=80 | | 0.25x^2-1/2x=1 | | 2x+3-5=-3 | | 18-(3x+5)=8 | | 10(a-1)-2(a+2)+3=13 | | 9(4-y)+2=-2(y-4)-3 | | 8x-1+4=6 | | .16(y-1)+.06y=.18y-.3 | | 7-6x/4 | | 7-4/x | | 5x-y=100 | | .75x+.05(20-x)=.10(-46) | | x^2+16=64 | | 4p+7=12+3p | | 7.6x+3=6.6x | | r=51-2r | | (4x+5)(3y-7)= | | 6(4-3)-5(4+2)=8 | | x^2-5x=2x^2+x | | 6x+3.9=53.1 | | (x^3+11x^2+18x)/(x^2-6x-16) | | .06x+.03(6000-x)=219 | | (9z^2+30z+25)/(9z^2+9z-10) | | (-2/w+4)=(-5/2w+8)+2 | | 4^(3/2) | | (t^2-16)/(t-4) | | Wxy+6=a | | 7x+10+x+20+2x=180 |